Social Female Adaptation / Resocialization in the Russian Reality - Gataullovich Minzaripov, Riyaz (2021)
Adaptation to the conditions of freedom and the resocialization of persons who served their terms is determined by a gender factor, especially in societies with a bright masculine characteristic, to which the Russian society belongs too. In such societies, the process of female post-penitentiary adaptation is more complicated, because it, as before, is dominated by a more negative attitude to female crime than to male one. This is a reflection of the specifics of a society of a masculine type, where the system of double standards influences public consciousness and determines the attitude towards persons who broke the law depending on their gender. Thus, the post-penitentiary female resocialization in Russia occurs under the influence of a combination of factors and difficulties that are typical for this period of women’s lifetime, typical of ex-prisoners in Russia and connected with a specific attitude of the society to female crime as well. This situation, in many respects, determines an unsuccessful scenario of the process of post-penitentiary female resocialization and, as a result, increases risks of recurrent crime in the female environment in the modern Russian society